When violence touches: the soundscape in the reception of the work of art - Guerra, Paula; Oliveira , Jaqueline Torquatro de; Dala , Jovani; Kumm, Rosely (Farol, 2024)
Can the ambient sound of an exhibition space influence the apprehension of the work of art? Through Schafer (1977) with his concept of soundscape - and supported by Cage (1961) in his concept of active listening Cage (1961) -, we will engage in an interlocution with the exhibition “Projéteis” (2009) by Marcelo Gandini. The sound becomes an active part of the work, creating an immersive environment that goes beyond visuality, promoting a deeper interaction with the space and intensifying the aesthetic and emotional experience of the work.